Some Binary Complexes of Cadmium(II) and Manganese(II) - Bask, Devshish (Asian Journal of Chemistry, 2010)
Interaction of cadmium(II) and manganese(II) with o-, m- and p- aminobenzoic acids has been investigated by paper electrophoresis in aqueous medium at 25 ± 1ºC at a fixed ionic strength μ= 0.1 M HClO4. The stability constants of Cd(II) complexes are higher than those of Mn(II) complexes which is in accordance with the Irving-Williams order.